Essential Oil Composition of Thymus eriocalyx (Ronniger) Jalas from Turkey - Zehra Kucukbay, F.; Kuyumcu, Ebru (Asian Journal of Chemistry, 2010)
Hydrodistilled volatile oil from the aerial parts of Thymus eriocalyx (Ronniger) Jalas was analyzed by a combination of GC and GC-MS. Seventy compounds were identified, representing 98.54 % of the oil. The major components were found to be thymol (47.79 %), β-caryophyllene (11.98 %), 1,8-cineole (9.88 %), borneol (3.88 %), p-cymene (3.02 %), carvacrol methyl ether (2.99 %), γ-terpinene (2.97 %) and germacrene D (2.83 %).